Much Ado about nothing? A multilevel analysis of the relationship between voluntary associations' characteristics and their members' generalized trust. Issue 1 (2nd January 2016) - Lindberg, Elisabet; Farkas, Gergei M.
ABSTRACT: The last 20 years of research on the micro-level relationship between involvement in voluntary associations and generalized trust has been characterized by a growing theory–data gap. This gap is especially problematic in terms of including diversity across voluntary associations in empirical analyses. This article aims to bridge this gap by using a hierarchically clustered data set (active members nested in voluntary associations) and multilevel analyses to test several hypotheses drawn from prior studies about the relationship between voluntary associations' characteristics and members' level of generalized trust. Overall, the results indicate that in explaining the variability in individual generalized trust levels, differences among the associations in which individuals are involved could contribute marginally at best. Almost all variance (97.6%) in individual level of generalized trust lies between the individuals and not between the associations. Furthermore, the analyses show no correlations for most tested associational characteristics. As for membership diversity, the most pronounced result runs opposite to expectation—thus providing some support for a membership similarity hypothesis rather than for a diversity hypothesis. The article raises the question whether the search for associational differences that might explain the lack of a general relationship between membership in voluntary associations and individual level of generalized trust is in fact a dead end.